DISCOURSE OF QUALITY EDUCATION IN PUBLIC JUNIOR HIGH SCHOOLS IN DENPASAR CITY - Narsa, I Nengah (E-Journal of Cultural Studies, 2015)
This present study was conducted to understand the discourse of quality education in Public Junior High Schools in Denpasar City. The study focused on the discourse of quality education in the practice of enrollment of new learners, the implementation of ‘ Kurikulum Tingkat Satuan Pendidikan’ , and the implementation of the National Final Examination in Public Junior High Schools in Denpasar City. The collected data were analyzed qualitatively and interpretatively. The theory of discourse of power/knowledge, the theory of social practice, and the theory of School-based Management were eclectically used in the present study. The results of the study showed that, first, the practice of the enrollment of new learners ‘ Praktik Penerimaan Peserta Didik Baru (PPDB) ’, Educational Unit-based Curriculum ‘ Kurikulum Tingkat Satuan Pendidikan (KTSP) ’, and the National Final Examination ‘Ujian Nasional (UN)’ which tended to neglect the principle of School-based Management (MBS) and the school autonomy had led to the discourse of quality education in Public Junior High Schools ‘Sekolah Menengah Pertama (SMPN)’ in Denpasar City; second, the ideology which was referred to in the discourse of quality education which was related to PPDB, KTSP and UN in public junior high schools in Denpasar City was the liberal ideology which was based on rationalism, individualism and commercialism; third, the discourse of quality education in public junior high schools in Denpasar City had theoretical implication, namely, there was an expectation to reinforce the ideology of critical-cultural education and to establish the paradigm of political policy which supported the attempt made to realize quality education.
Keywords: Discourse, quality education, ideology, school autonomy.